2007
DOI: 10.1111/j.1468-2982.2006.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Tension-Type Headache Over a 12-Year Period is Related to Increased Pain Sensitivity. A Population Study

Abstract: We recently reported an increase in prevalence and frequency of tension-type headache (TTH) over a 12-year period in the young Danish population. The aim of the present study was to analyse whether this increase was related to increased pain sensitivity. The study was a cross-sectional replicate of a large Danish population study. It compared 113 subjects aged 25-36 years in 2001, with 221 comparable subjects in 1989. Tenderness was considerably higher in 2001 than in 1989. When stratified according to presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 25 publications
(45 reference statements)
2
23
0
5
Order By: Relevance
“…The data from these clinical studies recently were confirmed in a population-based study demonstrating a close relation between altered pain perception and chronification of headache [13]. In addition, it was demonstrated that a previously reported increase in TTH prevalence over a 12-year period was related to increased pain sensitivity [53].…”
Section: Central Pain Sensitivitymentioning
confidence: 83%
“…The data from these clinical studies recently were confirmed in a population-based study demonstrating a close relation between altered pain perception and chronification of headache [13]. In addition, it was demonstrated that a previously reported increase in TTH prevalence over a 12-year period was related to increased pain sensitivity [53].…”
Section: Central Pain Sensitivitymentioning
confidence: 83%
“…to begin with, suggesting that it is a consequence rather than cause [11]. There are many studies showing decreased pressure pain thresholds [12], while others have shown an inverse relation between pericranial tenderness and pain threshold [13].…”
Section: Mattoo Et Almentioning
confidence: 99%
“…It has been thought that sustained peripheral nociceptive inputs through sensitization of central mechanisms increase sensitivity to painful stimuli, ultimately resulting in TTH [6,7]. …”
Section: Introductionmentioning
confidence: 99%